ANOMALI GAYABERAT DAN POTENSI BENCANA GEOLOGI DI KAWASAN JAWA BARAT BAGIAN TENGAH - Subagio Subagio (Pusat Survei Geologi, 2013)
In the Central part of West Java, anomaly Bouguer values vary from 5 to 125 mGals, forming high and low anomalies. The lowest anomaly located around Tagogapu, Padalarang area showing a sediment basin; while the highest anomaly is located around Pelabuhanratu, that are controlled by the existence of ultramafic rocks. In the survey area the rocks are divided into three groups, involving Tertiary sedimentary rocks with density 2,4 gr/cm3; Quaternary volcanic rocks with density 2,2 gr/cm3; and andesite with density 2,8 gr/cm3. Based on the modellings, faults in this area consist of thrust, normal and strike slip faults, partly are active faults. In Puncak area and its surroundings are a graben zone, that filled by low density rocks consisting of Quaternary volcanic rocks, is controlled by sub-surface active faults. Therefore the areas potentialy undergo landslides.Key words: gravity anomaly, active faults,Puncak, graben zone, landslide